A new species of Proablepharus (Scincidae: Lygosominae) from Mt Surprise, north-eastern Queensland, Australia - Couper, Patrick J.; Limpus, Colin J.; Mcdonald, Keith R.; Amey, Andrew P. (Zootaxa, 2010)
Proablepharus barrylyoni sp. nov. is described from a single locality near Mt Surprise, north-eastern Queensland. It is distinguished from its congeners by the following character states: body longitudinally striped, four supraoculars, five supraciliaries, frontoparietals fused to interparietal, upper preocular well-developed, two postsupralabials, lamellae beneath digits of pes smoothly rounded. The species was last collected in 1981 and, using criteria prescribed in the Queensland Nature Conservation Act, Wildlife Regulation 1994, qualifies as Vulnerable.